IMPROVEMENT OF KNOWLEDGE RELATED TO CORONAVIRUS DISEASE (COVID-19) - Kusuma Wijaya Ridi Putra (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health promotion activities about COVID-19 through the installation of banners are an activity in order to provide information related to the COVID-19 pandemic. The banner installation was carried out starting from April 20, 2020, which is located at 3 points in Gelam Village, Sidoarjo Regency. After the banners were installed at these 3 points, the residents whose houses were near the installation of the banners gradually changed their behavior who cared about preventing the spread of Covid-19. Changes in behavior include providing a place to wash hands before entering the house and prayer room, wearing masks when leaving the house, avoiding crowding, and signaling the mosque for physical distancing.